Enhancing Project Management Practices through Risk Management Policies at Finnbox Post Oy - Jami, Thungchanbeni (My University, 2025)
My thesis aims to improve project management practices through risk management policies at Finnbox Post Oy, a small-scale postal logistics firm based in Seinäjoki, Finland. The research aims to investigate how risk governance frameworks with structure can enhance operational resilience and efficiency in digitally dependent logistics operations. The research develops and implements the Finnbox Lightweight Risk Governance Cycle (FLRGC) as a lightweight, scalable model to tackle persistent issues in small logistics firms. The operational challenges examined in this thesis consist of software failures during delivery, human errors in sorting, incorrect or delayed shipments, communication breakdowns, and unstructured risk identification procedures. The existing literature provides risk management strategies for large-scale supply chains, yet it lacks sufficient information about adapting these principles to smaller firms operating in resource-constrained environments. The research adopts a qualitative case study design which combines a systematic literature review with six semi-structured interviews that were conducted through the University of Vaasa’s Webropol platform. The research involved delivery drivers, sorting staff and a supervisor who provided comprehensive insights into organizational challenges and response patterns. The research findings are evaluated utilizing PMBOK risk management guidelines along with Contingency Theory and Supply Chain Risk Management (SCRM) models. The research reveals five thematic risk areas that require strategic interventions that include formalizing risk frameworks, real-time Key Risk Indicators (KRIs) tracking, strengthening training and SOPs, and implementing feedback loops and sustainable last-mile delivery solutions. The FLRGC model combines these elements into a practical cyclical governance tool that works for small postal/logistics firms. The research provides both theoretical and practical knowledge for project professionals who are engaged in logistics-intensive service sectors. The research provides a duplicate model for small and medium enterprises (SMEs) to link operational risk control with scalable project management practices for maintaining business continuity and customer satisfaction.
Keywords: risk management; risks; logistics; project management; small and medium-sized enterprises; project leadership; fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master's Programme in Industrial Management; Strategic Project Management